Refugee Women's Experiences With Sexual Violence and Their Post-Migration Needs in Canada - Silva, Jessica (Université d'Ottawa / University of Ottawa, 2015)
Sexual violence is a prominent issue worldwide, especially during times of war and conflict. For refugee women, experiences with sexual violence are often incorporated in women’s reasons for forced migration. During the immigration process to Canada, refugee women are asked to share their narratives, at which point they may or may not disclose their histories of sexual violence. In June 2012, the Canadian government made substantial cuts to the Interim Federal Health Program. For refugee women who are survivors of sexual violence, this means that they are further limited in accessing services they might require in order to deal with the sexual violence they have experienced. Drawing from interviews we conducted with key informants (n=15) and refugee women (n=12) in both Toronto and Ottawa, this thesis explores both the lived experiences of refugee women and the changes, if any, that should be made to current service delivery. Our results show that there is a pronounced need for both small- and large-scale improvements at the systems and service delivery levels.
Keywords: Refugees; Asylum seekers; Sexual Violence; Resettlement; Counselling; Gender-based violence; Refugee health; Integration services